Management of Vitamin D Deficiency in Children: An Update - Begum, Suraiya; Shyamaly, Kohinoor Jahan; Tithi, Baraka Badrudduza; Ahkter, Romana Omana; Parvin, Rukhsana; Karim, Muhammad Rejaul; Jannat, Ismat Ara (Bangladesh Journal of Child Health, 2020)
Vitamin D is a steroid hormone that plays a major role in maintaining skeletal health and it also has a role in disorders other than bone metabolism. In the paediatric population, vitamin D deficiency has emerged as a significant public health problem throughout the world and majority of children has vitamin D deficiency in spite of wide availability of sunlight. Vitamin D deficiency status is defined as deficiency when 25(OH)D level is less than 30 ng/mL (75 nmol/L) The manifestations of deficiency may vary from hypocalcemic seizures and tetany in infancy, florid rickets in toddlers, and pain in adolescent. Vitamin D deficiency is associated with other different clinical diseases, such as, insulin resistance, metabolic syndrome, respiratory tract infections, asthma, and autoimmune diseases. It is also associated with prematurity, obesity, malabsorption, extreme latitudes and little sunlight exposure. Routine supplementation of vitamin D starting from newborn period is endorsed by various international organizations. Prevention by adequate sunlight exposure, food fortification and routine supplementation are the currently available options for this nutritional deficiency. In conclusion, vitamin D deficiency is highly prevalent in the paediatric age group. Aim of this review article is to discuss the health benefits of vitamin D and to provide recommendations for the prevention and treatment of vitamin D deficiency. Bangladesh J Child Health 2019; VOL 43 (3) :165-173